The true cost of information security breaches and cyber crime - Krausz, Michael; Walker, John (IT Governance Pub., 2013)
This pocket guide uses case studies to illustrate the possible breach scenarios that an organisation can face. It sets out a sensible, realistic assessment of the actual costs of a data or information breach and explains how managers can determine the business damage caused.
Print version record
Keywords: Business enterprises -- Computer networks -- Security measures; Computer security -- Management; Data protection -- Case studies -- Economic aspects; Computer crimes -- Case studies -- Economic aspects; Sécurité informatique; Gestion; Protection de l'information (Informatique); Aspect économique; Études de cas; Criminalité informatique; Aspect économique; Études de cas; COMPUTERS; Security; General; Business enterprises; Computer networks; Security measures; Computer security; Management; Case studies